Some Characteristics of Our Prose Works in Oriental Languages - Ljubović, Amir (Prilozi za orijentalnu filologiju, 2017)
Within the broad researches in our prose works in oriental languages the whole inventory of that part of our kultural inheritance has been examined, and for the need of these researches a 160 works small and large volumes has been selected. The basic criterions for the selection were: the indisputable historical identity of the author and the indisputable identity of the work and the authorship. Beside this, only compositions that make an entirety, those kept untill today in one or several copies, which we were able to consult directly or through the catalogue, and also some unfound works known according to reliable sources have been taken into consideration. After the analysis of the forms and contents of these texts we came to a number of conclusions also approved by some quantitative indications. The great part of these works consists of didactic, scientific and specialized literary works, mostly of textbook character. Therefore the function of these literaz works was to educate and to spread science. From the beginning of the 16 century (when our first important authors appeared) in both fields particular importance has been attached to theologie and law disciplines on one side, and to the linguistics on the other side. Therefore, these disciplines take part in the whole inventory with 50% (36% + 17%). Among the other disciplines the participation of logics as general propedeutics (15%) has to be emphasised, whereas physical sciences and mathematics were represented very poor. As regards to the part of prose works which purpose was not didactional, we may say it mostly appears in traditional literary works of memorial characters. These are, in the first place, chronicles, histories, hagiographies, autobiographies, travelogues. The so called political papers siyaset name also belong to this group (with more or less philosophie or sociologic character). The general characteristic of this part of the prose work is that it was turned to its milieu much more than the previous parts. Finally, about 8% of the inventory consists of compositions from belletristic literature, and commentaries on prose and poetry. Contents we were talking about were mediated by various forms which we classified into seven groups: short compositions, independent works, commentaries, supercommentaries, glasses, superglosses, adaptations, shortened versions and compilations. There is a table in this paper which clearly shows how correlative are the forms and the contents. It is noticeable that various types of commentaries, adaptations and compilations have the domination (58% of the inventory); and this shows that scientists and writers of that time were much more devoted to collecting, interpretation and sistematization, than to research something new. Also, most of the works that we conditionally called independent (26%) has didactic character (text book, compediums). It is understandable that biographies, autobiographies, chronicles, histories and travelogues are completely original works. Short compositions, mostly in form of "risāla", are in great part tractates of four pages about some theologie and law questions.